FAKTOR DAN BENTUK KEKERASAN TERHADAP PEREMPUAN DI KOTA TANJUNGPINANG - Sari, Afna Fitria (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine the factors and forms of violence against women in Tanjungpinang and what actions should be taken when finding symptoms or experiencing violence against women that occur in the surrounding environment. Using descriptive qualitative research methods, by carrying out several stages, namely: starting with observation as a research mapping, followed by drafting questions as a reference for interviews with related parties, as a final stage in completing the research, a literature study is carried out to strengthen the data described. The research found several factors that influence the occurrence of violence against women in Tanjungpinag. Such as sociocultural conditions and understanding of the patriarchal culture that develops in society, and the quality of human resources related to the emotional maturity of married couples so that physical neglect occurs. Meanwhile, forms of violence against women include physical, psychological, economic, and sexual violence. This research also invites the community to be responsive to the issue of violence against women that occurs in Tanjungpinang.